(untitled) (Comillas Journal of International Relations, 2020)
The smuggling of people from West Africa to Europe has increased considerably over the last lustrum, becoming a key component of the international political agenda. The drowned voices in the Mare Nostrum, and Europe’s scarce capacity to respond to this situation require a new, more humane, reflection in the academic study of this hot topic. This work aims to delve into one of the crucial and least studied aspects of the smuggling process: the functioning of the smuggling networks currently operating in West Africa. That is, how the journey from the country of departure takes place to, in the case of our research, Libya, the country of connection with Europe. The study of this topic from an academic perspective aims to constitute a tool that facilitates the understanding of the transcendence of the problem and favours the creation of projects that approach the situation from a holistic perspective.